Formulasi Dan Evaluasi Sifat Fisik Sediaan Kondisioner Ekstrak Air Kelapa Dengan Metode Freeze Drying - Azmi Rahmadani; Yuyun Darma Ayu Ningrum; Rizal Roffada Hanif; Khusnul Berty Indartantri (Sains Medisina, 2023)
Coconut water contains minerals, vitamins, sugars and essential amino acids which are beneficial for the body including hair. Coconut water can provide benefits including nourishing and moisturizing hair because it contains lauric acid. In addition, coconut water contains vitamins C and B which are good for increasing the production of keratin and collagen in hair as well as antioxidants, therefore coconut water extract is formulated into conditioner preparations. This study aims to determine the formulation of coconut water extract conditioner using the freeze drying method, as well as to find out the results of its physical evaluation. Determination of differences in concentrations of stearic acid and triethanolamine using the Simplex Latex Design (SLD). Physical evaluation includes organoleptic test, homogeneity test, dosage type test, pH test, viscosity test, and stability test. After testing the 8 formulas, Formulas 4, 5, and 7 were obtained as optimal formulas. The results of the stability test showed that the three formulas were stable in terms of the organoleptic test results and good homogeneity with the M/A preparation type. The three formulas have a pH of 6 and the viscosity value of formula 4 is 45550, formula 5 is 45140, formula 7 is 45000 which meets the requirements for a good conditioner preparation. Keywords: Coconut water, Freeze drying, Conditioner